Exploring the Association Between Triglyceride-Glucose Indices and Their Derivatives With Obstructive Sleep Apnea: Insights From the National Health and Nutrition Examination Survey - Zhou Y; Xue F (Nature and Science of Sleep)
Yating Zhou,* Fei Xue* Kunshan Hospital of Traditional Chinese Medicine, Kunshan City, Suzhou, Jiangsu Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fei Xue, Department of Surgery, Kunshan Hospital of Traditional Chinese Medicine, Zuchongzhi South Road, Kunshan City, Suzhou, Jiangsu, 215300, People’s Republic of China, Email 2090168460@qq.comBackground: Simple and affordable methods for evaluating Insulin Resistance (IR) have been suggested, such as the Triglyceride-Glucose (TyG) index and its variants, including the TyG-Body Mass Index (TyG-BMI), TyG-Waist Circumference (TyG-WC), and TyG-Waist-to-Height Ratio (TyG-WHtR). The aim of this study is to investigate the relationship between these TyG-related indices, which measure IR, and Obstructive Sleep Apnea (OSA).Methods: This study analyzed NHANES data from 2007– 2008, 2015– 2016, and 2017– 2020. TyG and its derivatives were evaluated as continuous and categorical variables in relation to OSA using multivariable logistic regression models. Subgroup analyses, dose-response relationships, and threshold effects were explored, and the diagnostic performance of TyG-related indices was assessed using AUC curves.Results: The study included 8,374 participants. The fully adjusted Model 3 analysis (Note: Body Mass Index was not adjusted for TyG-BMI) of continuous variables showed a positive correlation between OSA and all four indices. All four TyG-related indicators showed statistically significant relationships with OSA when grouped into quartiles (TyG: AOR = 1.448, 95% CI: 1.260– 1.663; TyG-BMI: AOR = 3.785, 95% CI: 3.319– 4.317; TyG-WC: AOR = 2.089, 95% CI: 1.629– 2.677; TyG-WHtR: AOR = 1.913, 95% CI: 1.548– 2.363). Subgroup analysis revealed a stronger association of TyG-WHtR with OSA in the 41– 59 age group (AOR = 1.459, 95% CI: 1.254– 1.698) and the low-income group (AOR = 1.451, 95% CI: 1.241– 1.698). TyG showed a linear relationship with OSA, while TyG-BMI, TyG-WC, and TyG-WHtR exhibited nonlinear relationships. The diagnostic capability was highest for TyG-WC, with an AUC of 0.647.Conclusion: The study confirms strong associations between OSA and the TyG indices, particularly TyG-WC, which demonstrates significant predictive power for OSA risk. Future longitudinal studies are recommended to further investigate these associations and enhance OSA management in resource-constrained environments.Keywords: triglyceride-glucose index, insulin resistance, epidemiological study, metabolic indices, obstructive sleep apnea